Mechanistic insights into the adsorption of endocrine disruptors onto polystyrene microplastics in water. (15th February 2023) - Cortés-Arriagada, Diego; Ortega, Daniela E.; Miranda-Rojas, Sebastián
Abstract: Microplastics and endocrine disruptors (EDs) are contaminants of emerging concerns and ubiquitously present in aquatic ecosystems, establishing interactions that still are the subject of investigation due to their implications in the cotransport of pollutants. Then, we conducted mechanistic studies based on state-of-art computational chemistry methods to quantitatively understand the interaction mechanisms whereby polystyrene micro or nanoplastics (PS-MPs) interact with representative classes of EDs in water (Ethynylestradiol, Estradiol, and Bisphenol A). The results showed that PS-MPs increase their charge distribution when forming microparticles in water, giving a permanent dipole that explains their increasing solubility in aqueous conditions. In agreement with experimental assessments, the PS-MPs favorably adsorb EDs with adsorption energies larger than 15 kcal/mol, even with comparable stability to nanostructured materials for adsorption, removal, and/or analysis of pollutants. The adsorption occurs via physisorption without covalent binding, bond breaking, or structural preparation energies, where the molecular structure of EDs can favor inner or outer surface adsorption depending on the molecular structure of the adsorbates. A balanced contribution of dispersion and electrostatic stabilizing effects determines the interaction mechanisms, accounting for a whole contribution of 88–90%. The electrostatic contribution emerges from the favorable alignment of the PS-MPs and EDs dipoles upon interaction due to the mild charge transfer between them in solution. In contrast, the dispersion contribution emerges from electron-electron interactions due to the permanent dipoles in adsorbates and adsorbents. Furthermore, thermochemical analyses clarify the role of temperature and pressure effects on the relative adsorption stability among EDs in aquatic environments. Therefore, modeling the adsorption process contributes to new knowledge on the sorption properties of PS-MPs, providing a mechanistic basis to understand the cotransport of pollutants in water environments and their impacts on environmental pollution. Graphical abstract: Image 1 Highlights: Polystyrene microplastics (PS-MPs) become polarized in water and upon interaction. The EDs-PS-MPs interactions are thermodynamically allowed only via physisorption. Dispersion and electrostatic stabilizing effects drive the interaction mechanism. The temperature and pressure determine the relative adsorption stability among EDs.